TIP OF THE TONGUE IN INDONESIAN CLASSES OF VERBS, NOUN AND ADJECTIVES BETWEEN MALE AND FEMALE: TIP OF THE TONGUE DALAM BAHASA INDONESIA BERKELAS KATA VERBA, NOMINA, DAN ADJEKTIVA PADA LAKI-LAKI DAN PEREMPUAN - Elvira Rachmasari Aulia; Irwan Suswandi (LLDIKTI Wilayah X, 2023)
This research discusses tip-of-the-tongue between male and female speakers, especially in the word classes of verbs, nouns and adjectives. The purpose of this research is to analyze the frequency of the emergence of tip-of-the-tongue conditions in Indonesian with verb, noun and adjective word classes by male and female speakers. This research can be categorized as descriptive qualitative research using independent network theory. The data collection technique was conducted using quantitative and qualitative analysis techniques. Meanwhile, cakap semuka method used was the method using face-to-face interview. The results show that the effect of the emergence of tip-of-the-tongue conditions on men and female is not significant because it can be caused by how many words each person has or how to use everyday language. This condition occurs because the language knowledge possessed is mixed with their respective local languages and the knowledge gained when someone has a hobby of reading.